America as second creation : technology and narratives of new beginnings - Nye, David E., 1946- (MIT Press, 2003)
"After 1776, the former American colonies began to reimagine themselves as a unified, self-created community. Technologies had an important role in the resulting national narratives, and a few technologies assumed particular prominence. Among these were the axe, the mill, the canal, the railroad, and the irrigation dam. In this book David Nye explores the stories that clustered around these technologies. In doing so, he rediscovers an American story of origins, with America conceived as a second creation built in harmony with God's first creation." "Nye draws on popular literature, speeches, advertisements, paintings, and many other media to create a history of American foundation stories. He shows how these stories were revised periodically, as social and economic conditions changed, without over erasing the earlier stories entirely. The image of the isolated frontier family carving a homestead out of the wilderness with an axe persists to this day, alongside later images and narratives. In the book's conclusion, Nye considers the relation between these earlier stories and such later American developments as the conservation movement, narratives of environmental recovery, and the idealization of wilderness."--Jacket